2008
DOI: 10.1177/0739986308322912
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religiosity, Gender, and Language Preference Acculturation on Sexual Activity Among Latino/a Adolescents

Abstract: The purpose of this study was to determine the main and interactive effects of religiosity, gender, and language preference acculturation on sexual activity among 570 Latino/a adolescents from the 2002 National Survey of Family Growth. Results indicated that adolescents who viewed religion as very important, had frequent church attendance, and had more traditional attitudes on sexuality were less likely ever to have sex compared with adolescents who were less religious. Those with frequent church attendance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 31 publications
6
50
0
1
Order By: Relevance
“…In particular, frequency of religious services attendance and having RAS had more robust association with sexual activity than just holding religion as very important. These findings were in concert with findings from other studies (Kirby 2002;Rostosky et al 2004) including a recent study of a subset of Latino adolescents from the NSFG 2002 dataset (Edwards et al 2008). The findings regarding sexual attitudes-that more religious attitudes were related to less sexual risk behaviorssupported what had been alluded to, but not clearly identified, in other studies (Fehring et al 1998;Lefkowitz et al 2004;Thornton and Camburn 1989).…”
Section: Discussionsupporting
confidence: 73%
“…In particular, frequency of religious services attendance and having RAS had more robust association with sexual activity than just holding religion as very important. These findings were in concert with findings from other studies (Kirby 2002;Rostosky et al 2004) including a recent study of a subset of Latino adolescents from the NSFG 2002 dataset (Edwards et al 2008). The findings regarding sexual attitudes-that more religious attitudes were related to less sexual risk behaviorssupported what had been alluded to, but not clearly identified, in other studies (Fehring et al 1998;Lefkowitz et al 2004;Thornton and Camburn 1989).…”
Section: Discussionsupporting
confidence: 73%
“…Among those who did not complete the "Human Sexuality" course, no change was visible in the three research variables. The relation found in this study between level of religiosity and extent of progressiveness in attitudes towards sexuality, is similar to that found in other studies in Israel [13] and in other countries [18,36,37,12,14,38]. These studies found that people who defined themselves as secular possessed more progressive attitudes than people who defined themselves as traditional or religious.…”
Section: Discussionsupporting
confidence: 79%
“…To date, most of the research related to sex and religious commitment has been in the context of exploring the relationship between religious beliefs and sexual attitudes and behaviors in adolescent populations (Buzwell and Rosenthal 1996;Edwards et al 2008;Leonard and Scott-Jones 2010;Luquis et al 2012;Penhollow et al 2005Penhollow et al , 2007Zaleski and Schiaffino 2000). However, little is known about how religion impacts sexual self-esteem, or the ways in which adult women subjectively experience their sexuality (Mayers et al 2003).…”
Section: Introductionmentioning
confidence: 99%